The Illusion of Absence in Magic Tricks. (June 2020) - Svalebjørg, Mats; Øhrn, Heidi; Ekroll, Vebjørn
Recently, a curious illusion of absence has been described, where the space behind an occluder is compellingly experienced as empty. This illusion is similar to illusions based on amodal completion in the sense that it refers to occluded portions of a visual scene and informal observations suggest that it may also be largely impervious to conscious knowledge. The aim of the present experiment was to test the hypothesis that the illusion of absence is cognitively impenetrable in the same way as amodal completion. Participants viewed magic tricks based on amodal completion, the illusion of absence, or attentional and reasoning misdirection and tried to infer the secret behind the tricks after one, two, or three presentations. The results show that the tricks based on the illusion of absence are very difficult to debunk, even after repeated presentations. In this regard, they are similar to tricks based on amodal completion but different from tricks based on attentional and reasoning misdirection. The participants also rated how magical they felt the tricks were. Surprisingly, the magic ratings tended to be quite high even in trials where the participants had already discovered the secret behind the trick. This unexpected finding may be taken to suggest that there may be two magical moments in the lifetime of a magic trick: In addition to the magical experience evoked by trick itself, discovering the secret behind the trick may also evoke an experience of impossibility.